2020
DOI: 10.1007/s00784-020-03256-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy evaluation of bracket repositioning by indirect bonding: hard acrylic CAD/CAM versus soft one-layer silicone trays, an in vitro study

Abstract: Objectives: Rapid development of digital technologies and 3D printing provide new tools for orthodontic indirect bonding. The purpose of this in-vitro study is to evaluate the clinical acceptability of hard CAD/CAM indirect bonding tray. Material & Methods: Ten soft silicone transfer trays and ten hard CAD/CAM trays were produced and 200 brackets were placed on them. The brackets were then transferred to twenty SLA-printed models by indirect bonding. These models were scanned and digitally compared to the refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 26 publications
5
63
1
6
Order By: Relevance
“…This supports our results. Torque showed the worst transfer accuracies of all angular dimensions, and the same result was found in previous studies [ 5 , 7 , 14 , 16 ]. Nui et al refer to an excess of bonding material or the transfer tray design to explain the outcome for torque [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This supports our results. Torque showed the worst transfer accuracies of all angular dimensions, and the same result was found in previous studies [ 5 , 7 , 14 , 16 ]. Nui et al refer to an excess of bonding material or the transfer tray design to explain the outcome for torque [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…We evaluated the accuracy of 1453 brackets and tubes placed with IDB, while other studies analyzed between 136 and 300 brackets [ 5 , 6 , 7 , 8 , 14 , 15 , 16 ]. Most other studies investigated IDB from the central incisor to the first molar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Für die konventionelle indirekte Klebetechnik gelten Silikon-Trays als Goldstandard hinsichtlich der Übertragungsgenauigkeit [28,29]. Pottier et al konnten in einer in-vitro-Untersuchung zeigen, dass die Übertagungsgenauigkeit von Brackets mit im DLP-Verfahren hergestellten flexiblen Schablonen (Shore Härte 40D) klinisch akzeptabel waren, allerdings im Vergleich weniger genau als die der Silikon-Trays [30]. Auch wenn weitere In-vitro-Untersuchungen zu Erfolg versprechenden Ergebnissen kommen [26,31], werden weitere In-vitro-und anschließende klinische Studien benötigt, um eine fundierte Empfehlung geben zu können.…”
Section: Bracket-übertragungunclassified
“…More recently, computer-aided design/computer-aided manufacturing (CAD/CAM) transfer trays have been introduced [ 18 ], and studies of its accuracy have been conducted. It was suggested that the CAD/CAM transfer tray shows clinically acceptable results and is comparable to a silicone tray [ 19 ]. Xue et al also evaluated the accuracy of a newly designed bracket transfer device using CAD/CAM technology, and most of the measurements were within the clinically acceptable range, except for some brackets with torque deviation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%